A pilot study on the effects of pre-event manipulation on jump height and running velocity. Issue 11 (5th September 2006) - Shrier, I; Macdonald, D; Uchacz, G
Abstract : Purpose: To compare changes in jump height and running velocity with and without pre-event high-velocity, low-amplitude manipulation (HVLA). Methods: A crossover study design with elite healthy athletes was used. After a 15 min warm-up, the subjects were tested for countermovement jump height (CMJ) and flying 40 m sprint time (SPRINT). A sport chiropractor then evaluated each subject. Subjects were randomised to either HVLA (applied to joints based on examination) or placebo (simulated performance-enhancement stickers). They then rested for 60 min, performed another 15 min warm-up, and were retested. The protocol was repeated 48 h later with the alternative intervention. The mean of two sprints and three jumps were analysed, as well as peak performances. The sample size was based on prior results from the effects of stretching. Results: 19 subjects involved in sprint sports were enrolled; two were too sore to participate on day 2, and one could only participate in the jump (all had HVLA on day 1). Of the 17 participants analysed, seven were female, age range was 19–35, and 17 were national or world-class athletes. The ranges for baseline measures were: SPRINT 4.1–5.5 s; CMJ 47.4–92.7 cm. Overall, the greater than expected variability in this pilot study led to the study being underpowered. Subjects tended to perform better after HVLA for both CMJ and SPRINT (both mean and peak results), but none of the results were statistically significant (p = 0.30–0.61). Conclusion: Although the larger than expected variability in the pilot study means that the observed clinically relevant differences were not statistically significant, the direction and magnitude of the changes associated with HVLA suggest that it may be beneficial. That said, the increased soreness after HVLA suggests that it may be detrimental. HVLA warrants further study.